Reisseronia lesari sp. nov., R. gertrudae Sieder, 1962 and R. tarnierella (Bruand, 1850) in Slovenia (Lepidoptera: Psychidae) - Predovnik, Željko (Acta entomologica slovenica (Ljubljana), 2020)
The present study reviews the genus Reisseronia (Bruand, 1850)in Slovenia. Two species, R. gertrudae Sieder, 1962 and R. tarnierella (Bruand, 1850), are new to Slovenian fauna and Reisseronia lesari sp. nov. is described from Radensko polje in the central part of the country. The new species is parthenogenetic and is compared with several related taxa. Morphological differences are presented and shown in figures. Additional data about the habitat and biology of the discussed species are provided.
Keywords: butterflies; fauna; favna; Insecta; Lepidoptera; Metulji; new species; nove vrste; Psychidae; Reisseronia; Reisseronia lesari; Slovenia; Slovenija; Žuželke